A Review of bKash: Transforming Financial Inclusion and the Digital Economy in Bangladesh (The Science Post, 2025)
bKash, a Mobile Financial Service (MFS) established in 2010 as a joint venture between BRAC Bank and Money in Motion, has fundamentally reshaped the financial landscape of Bangladesh. This paper reviews the literature surrounding bKash's disruptive business model, its profound impact on financial inclusion, its diverse service offerings, and the challenges and opportunities it faces within the evolving FinTech ecosystem. By leveraging the country's high mobile phone penetration and extensive agent network, bKash successfully targeted the vast unbanked population, offering a secure, affordable, and convenient platform for basic financial transactions. The analysis highlights bKash's crucial role in poverty reduction, economic growth, and the acceleration of a cashless society, while also examining issues related to regulatory governance, market dominance, and technology-adoption barriers.